2006
DOI: 10.1242/jcs.03209
|View full text |Cite
|
Sign up to set email alerts
|

Different abilities of the four FGFRs to mediate FGF-1 translocation are linked to differences in the receptor C-terminal tail

Abstract: Members of the fibroblast growth factor family bind to one or more of the four closely related membrane-spanning FGF receptors. In addition to signaling through the receptors, exogenous FGF-1 and FGF-2 are endocytosed and translocated to the cytosol and nucleus where they stimulate RNA and DNA synthesis. Here we have studied the ability of the four FGF receptors to facilitate translocation of exogenous FGF-1 to the cytosol and nucleus. FGFR1 and FGFR4 were able to mediate translocation, whereas FGFR2 and FGFR3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
36
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 46 publications
4
36
0
Order By: Relevance
“…Recently, Sorensen et al (2006) demonstrated that a 50 amino acid sequence downstream of the tyrosine kinase domain in FGFR1 and 4 is required for the transport of fibroblast growth factor (FGF-1) from the plasma membrane to the cytosol and nucleus. Unlike FGFR1 and 4, FGFR2 lacks this sequence and consequently does not transport FGF-1 to the cytosol and nucleus (Sorensen et al 2006).…”
Section: Receptor Sequences For Subcellular Traffickingmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Sorensen et al (2006) demonstrated that a 50 amino acid sequence downstream of the tyrosine kinase domain in FGFR1 and 4 is required for the transport of fibroblast growth factor (FGF-1) from the plasma membrane to the cytosol and nucleus. Unlike FGFR1 and 4, FGFR2 lacks this sequence and consequently does not transport FGF-1 to the cytosol and nucleus (Sorensen et al 2006).…”
Section: Receptor Sequences For Subcellular Traffickingmentioning
confidence: 99%
“…Unlike FGFR1 and 4, FGFR2 lacks this sequence and consequently does not transport FGF-1 to the cytosol and nucleus (Sorensen et al 2006). Interestingly, mutation of two amino acids within FGFR2 (Q774M, P800H) is sufficient to allow FGFR2 to similarly transport FGF-1 (Sorensen et al 2006).…”
Section: Receptor Sequences For Subcellular Traffickingmentioning
confidence: 99%
“…The translocation of exogenous FGF1 or FGF2 into the cytosol and nucleus is a highly regulated process that requires phosphatidylinositol 3-kinase (PI3K) activity (23) and active hsp90 (52) and is strictly dependent on binding of FGF to either FGFR1 or FGFR4 (47). Furthermore, translocation was found to be cell cycle dependent (3,31,63), it can be stimulated by serum deprivation of cells (1,3,18,25,31,32,55,63), and it occurs after a several-hour delay compared to the endocytic uptake of FGF (31,47).…”
mentioning
confidence: 99%
“…Furthermore, translocation was found to be cell cycle dependent (3,31,63), it can be stimulated by serum deprivation of cells (1,3,18,25,31,32,55,63), and it occurs after a several-hour delay compared to the endocytic uptake of FGF (31,47). The nuclear trafficking of FGF1 is also tightly regulated by two nuclear localization sequences (19,51), a nuclear export sequence (36), and by phosphorylation of FGF1 at Ser130 by protein kinase C␦ (PKC␦) (57).…”
mentioning
confidence: 99%
See 1 more Smart Citation